PLAYFULNESS AS A PEDAGOGICAL RESOURCE OF SCHOOL PHYSICAL EDUCATION TO DEVELOP PSYCHOMOTRICITY THROUGH TEACHING (Fiep Bulletin - online, 2020)
The practice of swimming plays a major role in child psychomotor skills, as it enables the development of learning that contributes to the evolution of the child's physical, motor, cognitive and social development as it is considered a physical activity that enhances multiple motor skills through the stimulation of swimming movements. Thus, the following question arises: how to develop psychomotricity through swimming in children from 3 to 5 years old using the playful as the main methodological instrument of Physical Education? To answer this question, the present teaching and research project had as its theme: Playfulness as a pedagogical resource of Physical Education in order to develop Psychomotricity through the teaching of Child Swimming. And as a method the bibliographic research with the general objective of identifying the importance of the teaching of swimming in a playful way for the development of psychomotricity in preschool children, and with specific objectives to broaden the knowledge about this sport and to discuss the benefits of psychomotor activities in the aquatic environment for learning swimming skills. Thus, according to the study, playfulness when inserted in the teaching of swimming through games and games promotes the opportunity for children to challenge themselves, being able to create and discover various possibilities to perform movements in a fun way, which makes the playful aspect a capable facilitator. improve the child's development process, providing significant gains in physical condition, psychomotor development, socialization and the formation of a future critical and autonomous citizen.
Keywords: Playfulness; Child Swimming; Psychomotricity.